2020
DOI: 10.3390/nano10091680
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanowires on Single-Crystalline Aluminum Film Coupled with an Insulating WO3 Interlayer Manifesting Low Threshold SPP Laser Operation

Abstract: ZnO nanowire-based surface plasmon polariton (SPP) nanolasers with metal–insulator–semiconductor hierarchical nanostructures have emerged as potential candidates for integrated photonic applications. In the present study, we demonstrated an SPP nanolaser consisting of ZnO nanowires coupled with a single-crystalline aluminum (Al) film and a WO3 dielectric interlayer. High-quality ZnO nanowires were prepared using a vapor phase transport and condensation deposition process via catalyzed growth. Subsequently, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Table 1. Dielectric Constant and Lasing Threshold for Nanolasers with Different Dielectric Interlayers 13,18,36 The Table 1 summarizes the lasing threshold of the ZhDlA plasmonic nanolaser system with disparate dielectric constants compared with the other reported nanolaser system. The dielectric constant describes the capacitive charge, which can retain electrical energy created.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1. Dielectric Constant and Lasing Threshold for Nanolasers with Different Dielectric Interlayers 13,18,36 The Table 1 summarizes the lasing threshold of the ZhDlA plasmonic nanolaser system with disparate dielectric constants compared with the other reported nanolaser system. The dielectric constant describes the capacitive charge, which can retain electrical energy created.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In plasmonic nanolasers, surface plasmons coupled with photons confine light to the deep subwavelength area at the metal–dielectric material interface, enhancing light–matter interactions and supporting lasing modes much smaller than the optical wavelength. As a result, the dimension of the plasmonic cavity can be compressed to the nanometer scale, ultimately enabling the simultaneous amplification of photons. Various types of nanolasers have been demonstrated that possess many attributes for an on-chip light source such as low thresholds, , room-temperature operation, and dense-integration capability. Widespread efforts have been made to control the energy confinement between a metal–dielectric interface in metal–oxide–semiconductor structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc oxide (ZnO) nanomaterials have been extensively utilized as key components in important technological devices such as optoelectronic modules [ 1 , 2 , 3 ], nanolasers [ 4 , 5 , 6 ], strain sensors [ 7 , 8 ], biosensors [ 9 , 10 , 11 , 12 , 13 ], and multi-emission waveguides [ 14 ]. In particular, ZnO nanorods (NRs) have drawn considerable attention in the broad fields of photonics, biosensing, and light detection due to their exceptional optical properties that stem from the NRs’ reduced dimensionality and high shape anisotropy [ 4 , 7 , 9 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…also experimentally confirmed that a ZnO‐WO 3 ‐Al nanolaser structure has a lower nanolaser threshold than that of ZnO‐Al 2 O 3 ‐Al nanolaser structure. [ 17 ] However, it is worth noting that these SPPs waveguides usually have a large Ohmic loss and short transmission distance, due to the negative dielectric constant of metallic material. There is a trade‐off relationship between the transmission loss and optical field constraint in the SPPs nanolaser structure because of the Ohmic loss in metal substrate.…”
Section: Introductionmentioning
confidence: 99%